Socio‐demographic vulnerability to heatwave impacts in Brisbane, Australia: a time series analysis. (28th August 2014) - Toloo, Ghasem (Sam); Guo, Yuming; Turner, Lyle; Qi, Xin; Aitken, Peter; Tong, Shilu
Abstract Objective: Examining the association between socioeconomic disadvantage and heat‐related emergency department (ED) visits during heatwave periods in Brisbane, 2000–2008. Methods: Data from 10 public EDs were analysed using a generalised additive model for disease categories, age groups and gender. Results: Cumulative relative risks (RR) for non‐external causes other than cardiovascular and respiratory diseases were 1.11 and 1.05 in most and least disadvantaged areas, respectively. The pattern persisted on lags 0–2. Elevated risks were observed for all age groups above 15 years in all areas. However, with RRs of 1.19–1.28, the 65–74 years age group in more disadvantaged areas stood out, compared with RR=1.08 in less disadvantaged areas. This pattern was observed on lag 0 but did not persist. The RRs for male presentations were 1.10 and 1.04 in most and less disadvantaged areas; for females, RR was 1.04 in less disadvantaged areas. This pattern persisted across lags 0–2. Conclusions: Heat‐related ED visits increased during heatwaves. However, due to overlapping confidence intervals, variations across socioeconomic areas should be interpreted cautiously. Implications: ED data may be utilised for monitoring heat‐related health impacts, particularly on the first day of heatwaves, to facilitate prompt interventions and targeted resource allocation.